Disability, human rights, and information technology - Lazar, Jonathan; Stein, Michael Ashley; Brewer, Judy. (Philadelphia : Pennsylvania University of Pennsylvania Press, 2017)
"Disability, Human Rights, and Information Technology addresses the global issue of equal access to information and communications technology (ICT) for persons with disabilities. The right to access the same digital content at the same time and at the same cost as people without disabilities is implicit in several human rights instruments and is featured prominently in Articles 9 and 21 of the Convention of the Rights of Persons with Disabilities. The right to access ICT, moreover, invokes complementary civil and human rights issues: freedom of expression; freedom to information; political participation; civic engagement; inclusive education,... Despite the ready availability and minimal cost of technology to enable people with disabilities, practice around the glove continues to result in their exclusion." -- From the dust jacket.
Standards bodies, access to information technology, and human rights / Judy Brewer -- Accessible ICTs and the opening of political space for persons with disabilities / Janet E. Lord -- Web accessibility for people with cognitive disabilities : a legal right? / Peter Blanck -- Intersection of human rights, social justice, the internet, and accessibility in libraries : access, education, and inclusion / Paul T. Jaeger, Brian Wentz, and John Carlo Bertot -- Public financing of information technology and human rights for people with disabilities / Deborah Kaplan -- Using provincial laws to drive a national agenda : connecting human rights and disability rights laws / Ravi Malhotra and Megan A. Rusciano -- Access to justice / Fredric I. Lederer -- Open government and digital accessibility / Timothy Elder -- E-books and human rights / Jim Fruchterman -- Accessibility and online learning / Mary J. Ziegler and David Sloan -- Who owns captioning? / Raja Kushalnagar -- Information privacy and security as a human right for people with disabilities / Jonathan Lazar, Brian Wentz, and Marco Winckler -- How does inaccessible gaming lead to social exclusion? / Joyram Chakraborty -- Pivot model of policy entrepreneurship : an application of European ideas in the global South / G. Anthony Giannoumis, Mirriam Nthenge, and Jorge Manhique -- Accessibility infrastructure and the global South / Joyojeet Pal -- ICT access, disability human rights, and social inclusion in India / Sanjay S. Jain.
Includes bibliographical references and index.
Keywords: Information technology -- Social aspects; Computers and people with disabilities; People with disabilities -- Civil rights; Discrimination against people with disabilities; People with disabilities -- Services for -- Government policy; Accessible Web sites for people with disabilities; Communication devices for people with disabilities; Assistive computer technology -- Law and legislation; Right to Internet access; Accessible Web sites for people with disabilities; Assistive computer technology -- Law and legislation; Communication devices for people with disabilities; Computers and people with disabilities; Discrimination against people with disabilities; Information technology -- Social aspects; People with disabilities -- Civil rights; People with disabilities -- Services for -- Government policy; Right to Internet access